Arah Kebijakan Pangan Taiwan dalam Bingkai Kajian Politik Pangan - Anabarja, Sarah (Global and Policy Journal of International Relations, 2014)
ABSTRACTA country's food politics is an important factor that could determine whether the country couldsurvive or not to fed it’s people and at the same time promising a sustainable environment forit’s next generation. Therefore many issues concern with food and farming tend to be soaringin so many countries. the government’s performance and political system, the poverty, andpopulation growth level are some of the issues on surface as well as the the issues on food aidand environment issue. This paper explain about many issues shaping the food politics inTaiwan using the framework of food politics including food security dan food sovereignty.Keywords: Food Politics, Agriculture, Food Security, Food Sovereignty, Taiwan.DOI:https://doi.org/10.33005/jgp.v2i02.2068